The Pathways of Ideological and Political Education Integrated Throughout Business English Curriculum from the Perspective of Fostering Virtue - Feng, Doudou (Journal of Educational Research and Policies, 2024)
Fostering Virtue is the Fundamental Task of Education. Based on this fundamental task, universities should improve the teaching design of every course in various disciplines, integrating ideological and political education into them. This article explores the basic pathways for implementing ideological and political education in Business English courses from the perspective of fostering virtue. These pathways include establishing and dividing course groups for ideological and political education, exploring ideological and political elements to find corresponding material for integration, and innovating teaching methods to strengthen the effect of moral education. This article provides new ideas for integrating ideological and political education into Business English courses in universities.